Characteristic changes of ruminal fermentation in transition dairy cows - Park, A.F.; Titgemeyer, Evan C.; Cochran, R.C.; DeFrain, J.M.; Ferdinand, E.E.; Nagaraja, Tiruvoor G.; Johnson, D.E.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four-ruminally fistulated, multiparous, pregnant Holstein cows were used to delineate changes in ruminal fermentation in dairy cows as they experienced the transition from one lactation to the next. Diets consisted of typical far-off and close-up diets, a late lactation diet containing wet corn gluten feed (20% DM) and an alfalfa hay-corn silage based early lactation diet. Calculated NEL (Mcal/lb), measured crude protein (%), and diet digestibilities (%; based on steers fed at 2% of BW) were: 0.78, 18.7, 74.1; 0.70, 11.5, 66.2; 0.74, 15.6, 71.0; 0.73, 18.4, 70.7 for late lactation, far-off dry, close-up dry, and early lactation diets, respectively. Ruminal measurements were taken on days 72 (late lactation), 51 (faroff), 23, and 9 (close-up dry) before calving and on days 6, 20, 34, 48, 62, 76, and 90 days after calving. Ruminal samples were collected at hours 0, 3, 6, 9, and 12 after feeding on each sampling date. Major shifts in ruminal fermentations occurred when the close-up diet was consumed before calving and in concert with an increase in DM intake during the first 48 days of lactation. Dry matter digestibility increased after cows were switched to the close-up diet and continued this trend through day 6 postpartum. Ruminal pH decreased and total volatile fatty acids, peptides, and free amino acids increased after cows were switched to the early lactation diet. These data support the concept that alterations in ruminal fermentation reflect changes in both diet and intake.
Keywords: Dairy; Transition; Dairy cow; Rumen fermentation